A Bactrocera oleae (Rossi) damage estimation model to anticipate pest control strategies in olive production. (November 2020) - Martínez-Pertíñez, Ángel; Medina Vélez, Pilar
Abstract: The olive fly, Bactrocera oleae (Rossi), is the main pest in most olive-growing regions. During a 10-year study (2001–2011), olive fly population levels were evaluated in twenty olive groves in the region of Madrid, Spain, as part of the "European Program of Quality Improvement in Olive Oil and Table Olives". The fly population data obtained by trapping with McPhail traps throughout the season and the damage observed during fruit sampling were analyzed in order to obtain an easy-to-use and inexpensive damage estimation model that could then be used to predict the need for control measures. We observed that the increase in the number of adults caught in McPhail traps was significantly correlated with the increase in production damage. For the same increase in the olive fly population, there was more damage to the olive crop in the years when the date of appearance of the first stung fruit occurred later. Additionally, a significant correlation was obtained between the size of the olive fly population that caused the first damage and the size of the olive fly population that caused the total damage through the end of the harvest season. Therefore, the potential damage to the olive fruit crop at harvest time (usually in December) can be easily estimated in the middle of September by knowing the date that olive fly damage was first detected (first stung date) and by estimating the olive fly population size at the end of the season (obtained empirically from the population size when fruit damage was first detected). This means that prevention and control measures can be anticipated up to three months before the beginning of harvest. Highlights: Olive fly catches in McPhail traps were highly correlated with olive fruit infestations. Losses caused by olive fruit flies were higher when the date on which the first fruit was stung occurred later. The population size at time of the first fruit damage can be used to predict the size of the olive fly population at harvest. The first stung date and the estimated population were used to estimate losses at harvest time.